Konsep Consummate Love pada Novel "Cinta dalam Sujudku" Karya Diana Febi: Psikologi Sternberg - Mustafidatus Sholihah, Alvia; Indriyani, Jiphie Gilia (Jurnal Pena Indonesia, 2023)
Abstract: In creating a work of Islamic literature, the dominant author uses themes that contain romance. Of the many works in the form of Islamic novels, one of the works used as analysis in this study is the novel Cinta Dalam Sujudku by Diana Febi. This study describes the narrative flow that tells about romanticism with a religious theme in the novel Cinta Dalam Sujudku by Diana Febi. This Islamic novel narrates the romantic relationship with religious elements between the characters Zaki and Risa. This is what makes researchers interested in analyzing more deeply the types of love in the packaging of the novel Cinta Dalam Sujudku by Diana Febi. The purpose of this study is to identify the concept of the types of love in the novel. The method applied is descriptive qualitative method. The data analysis technique was carried out using the note-taking technique with literature study. The theory used in this study is the literary psychology theory of Robert John Sternberg's triangle of love. The researcher suggests that the relationship between the characters Zaki and Risa contains three main components in Sternberg's theory and includes the category of consummate love (true love). Keywords: Sternberg love psychology, Islamic novels, Cinta Dalam Sujudku, and consummate love.